Measurement and explanation of inequality in health and health care in low-income settings - Eddy van Doorslaer; Owen O'Donnell (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2008)
This paper describes approaches to the measurement and explanation of income-related inequality and inequity in health care financing, health care utilization and health and considers the applicability and the feasibility of these methods in low-income countries. Results from a comparative study of 14 Asian countries are used to illustrate the main issues. The structure of health finance in low-income countries, in particular the heavy reliance on out-of-pocket payments, means that the equity issues in finance are quite different from those of concern in high-income countries. Primary concern is not with the distribution of contributions to pre-payment mechanisms but with the deterrent effect of payments on utilization and the distribution of uninsured payment risks. Measurement of inequity in utilization of health care in low-income countries is constrained by the lack of reliable measures of health that can be used to standardize for need. Nonetheless, sufficient is known of the distribution of need in many circumstances in order to make inferences about equity from inequality in health care use. The empirical analyses demonstrate that, in low-income countries, the better-off tend to pay more for health care, both absolutely and in relative terms. But they also consume more health care. Health care is financed is largely according to the benefit principle. Assessing the distributional performance of health systems in low-income settings therefore requires examination of finance and utilization simultaneously.
Keywords: H22; H42; H51; 330; health inequality; equity